Genetic variability in samples of watermelon, Cirtullus lanatus (Thunb.) Matsum & Nakai, collected in six counties of the dry areas of Northeast Brazil - Queiroz, Manoel Abílio; Araújo, José Pires; Dias, Rita Cássia S. (SITIENTIBUS série Ciências Biológicas, 2002)
Forty-two watermelon seed samples were collected from six counties in the dry areas of the Northeast Brazil, particularly the states of Pernambuco, Bahia and Piauí, between 1985 and 1987. The samples were either from the farmer’s stock or from fruits of volunteer watermelon plants grown in the Experiment Stations of EMBRAPA in Petrolina, Pernambuco. Some accesses were evaluated for powdery mildiew and papaya ring spot virus-watermelon strain (PRSV-w) in 1987, 1988 and 1989. In 1987, in a field experiment, some seed samples were evaluated for fruit and plant characters (prolificacy, yield per plant, fruit shape and weight, flesh and seed color). Despite the limited area covered and few analysis performed, it was detected genetic variability for prolificacy, yield per plant, fruit shape and weight, flesh and seed color, resistance to powdery mildew and to PRSV-w. The promising accessions found can be used in crosses and selection programs in order to obtain adapted cultivars for the irrigated conditions of Northeast Brazil.